Thirty years of sowing hope to globalise the struggle: women and youth of La Via Campesina in the construction of food sovereignty – a conversation. Issue 2 (23rd February 2023) - Rodríguez, Francisca; Sosa Varrotti, Andrea P.
ABSTRACT: Since the 1990s, La Vía Campesina (LVC) has become one of the most important transnational movements in the world. Francisca 'Pancha' Rodríguez is one of the founders of both LVC and one of its regional expressions, the Latin American Coordination of Rural Organizations (CLOC), as well as of the National Association of Rural and Indigenous Women (ANAMURI), in Chile. In this article, she tells us about these movements' history and challenges, especially for peasant women and youth.